Salutary effects of adiponectin on colon cancer: in vivo and in vitro studies in mice. Issue 4 (26th June 2012) - Moon, Hyun-Seuk; Liu, Xiaowen; Nagel, Jutta M; Chamberland, John P; Diakopoulos, Kalliope N; Brinkoetter, Mary T; Hatziapostolou, Maria; Wu, Yan; Robson, Simon C; Iliopoulos, Dimitrios; Mantzoros, Christos S
Abstract : Background: Obesity and a high-fat diet are associated with the risk and progression of colon cancer. Low adiponectin levels may play an important role in the development of colon and other obesity-related malignancies. No previous studies have directly investigated the mechanistic effects of adiponectin on colon cancer in the settings of obesity, a high-fat diet and/or adiponectin deficiency. Objective: To investigate the effects of adiponectin on the growth of colorectal cancer in adiponectin-deficient or wild-type-C57BL/6 mice fed a low-fat or high-fat diet. Results: Mice fed a high-fat-diet gained more weight and had larger tumours than mice fed a low-fat-diet. Adiponectin administration suppressed implanted tumour growth, causing larger central necrotic areas. Adiponectin treatment also suppressed angiogenesis assessed by CD31 staining and VEGFb and VEGFd mRNA expression in tumours obtained from mice fed a high-fat-diet and from adiponectin-deficient mice. Adiponectin treatment decreased serum insulin levels in mice on a high-fat-diet and increased serum-interleukin (IL)-12 levels in adiponectin-deficient mice. In vitro, it was found that adiponectin directly controls malignant potential (cell proliferation, adhesion, invasion and colony formation) and regulates metabolic (AMPK/S6), inflammatory (STAT3/VEGF) and cell cycle (p21/p27/p53/cyclins) signalling pathways in both mouse MCA38 and human HT29, HCT116 and LoVo colon cancer cell lines in a LKB1 -dependent way. Conclusion: These new mechanistic and pathophysiology studies provide evidence for an important role of adiponectin in colon cancer. The data indicate that adiponectin or analogues might be useful agents in the management or chemoprevention of colon cancer.